Total neoadjuvant therapy for initially inoperable pancreatic cancer: A systematic review of phase 2–3 studies. (November 2021) - Tomasello, Gianluca; Ghidini, Michele; Ghidini, Antonio; Trevisan, Francesca; Celotti, Andrea; Russo, Alessandro; Gambini, Donatella; Indini, Alice; Rijavec, Erika; Bareggi, Claudia; Galassi, Barbara; Petrelli, Fausto
Highlights: Neoadjuvant treatments may convert inoperable pancreatic cancer to surgery. A total of 28 studies were included and analyzed. Total neoadjuvant therapy may convert to surgery about one third of patients. Optimal integration and sequence of chemo- and radiotherapy must still be defined. Abstract: Introduction: Patients with initially inoperable non-metastatic pancreatic cancer (PC) have a poor prognosis, often similar to those with metastatic disease. Neoadjuvant chemotherapy (CT) plus concomitant or sequential radiotherapy (RT) may cause tumor shrinkage and allow for radical surgery. We pooled data of studies in which patients with locally advanced (unresectable) or borderline resectable PC were treated with a course of induction (or consolidation) CT followed or preceded by neoadjuvant CTRT regimen. Materials and methods: We searched articles, including phase 2 or 3 studies, published in English from 2010 up to December 2020 in PubMed, SCOPUS, the Cochrane Library, and EMBASE. The primary outcomes were the pooled radical and R0 resection rates, median PFS and OS of included patients (those included in the intent to treat analysis). Results: A total of 28 studies were finally considered eligible for inclusion in quantitative analysis for a total of 2446 patients with locally advanced/borderline resectable PC. Overall the pooled rate of resection was 29.7% (95%CI 26.7–32.8%). In patients who completed the CT + CTRT program, the overall resection rate was 31.8% (95% 28.4–35.4%). After exclusion of studies that included resectable PCs, the overall resection rate was 19.9% (95%CI 17.3–22.7%). In studies were all patients had unresectable PC ( n  = 20 studies), the resection rate was 12.1% (95%CI 10–14.5%). In two studies that enrolled all borderline resectable PCs the resection rate was 59.2% (95%CI 48.9–68.8%). The pooled R0 resection rate was 68.7% (95%CI 64.7–72.3%). The median pooled OS was 15.7 months (95%CI 14–17.2 months) and the median pooled PFS was 10.7 (95%CI 9.3–12.1 months). Conclusions: Surgery is a treatment option in about one third of patients with initially inoperable PC, following total neoadjuvant therapy. In unresectable cases the resection rate was 12%. Median OS and PFS rates were comparable with historical data of advanced PCs. Optimal integration and sequence of chemo- and radiotherapy in unresectable PC must still be defined.